(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article compares Konstantin Stanislavski’s 1938 book, Rabota aktiora nad soboi, Tchast I (The Actor’s Work on Himself, Part I), with Elizabeth Reynolds Hapgood’s English translation that was published in 1936, An Actor Prepares. The comparison reveals significant differences ranging from the size of the text, which indicates a strong editorial abridgment, to changes or inconstancies in the choice of certain terminology. Thus, the article focuses on the consequences that this translation brought for the understanding of the "system" in the US theater, especially in the 20th century, and how the choices made by the editorial board and the translator were decisive during the transmission and the change of meaning of Stanislavski’s text and, therefore, of his ideas.